INHIBITORY ACTIVITY OF ZINGIBER OFFICINALE VAR RUBRUM EXTRACT AGAINST STAPHYLOCOCCUS AUREUS - Dewi, Firnanda Iptita; Wahyunitisari, Manik retno (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: gram-negative bacteria-salmonella typhi and gram-positive bacteria-staphylococcus aureus are types of bacteria that cause infectious disease among several areas in Indonesia. Staphylococcus aureus often found in skin lesions injury. Red ginger extract (Zingiber officinale var rubrum) has been known for its medicinal value especially as an antibacterial agent. Purpose: This study aims to test the ability of Zingiber officinale var rubrum on inhibiting the growth of Staphylococcus aureus. Methods: the activity of the antibacterial agent was calculated based on Minimum Inhibitory Concentration (MIC) using dilution method. Minimum Inhibitory Concentration of extract was determined by incubating bacteria with the extract overnight at 37 0C. Changes in turbidity and inhibition on bacterial growth were then observed. Result: The results show that minimum concentration for inhibitory effect was 1000 Î¼g/mL. Conclusion: extract of Zingiber officinale var rubrum have an inhibitory effect on the growth of Staphylococcus aureus but no activity of killing bacterial was observed on the concentration given.